Leveraging Emerging Technology to Design an Inclusive Future with Universal Design for Learning - Don Douglas McMahon; Zachary Walker (Center for Educational Policy Studies Journal)
The aim of this article is to explore the opportunities and challenges that arise with the proliferation of new technology, to provide an understanding of why it is important to try new strategies in education, and to provide an inclusive framework for experimentation using tools such as robotisation, automatisation, artificial intelligence and immersive learning. Significant challenges exist in implementing transformative technologies with a limited or non-existent evidence base for their use, and designing inclusive educational experiences with a limited evidence base is even more challenging. In order to address this need, the article presents some ways in which educators can make informed implementation decisions around these new tools. First, we examine the rule of the least dangerous assumption, which supports trying new technologies even if the evidence base is lacking. Next, we present a strategy that educators can use to apply the research-based framework of UDL in order to make informed implementation choices with new technologies. Finally, based on information gained from experience in providing professional development, school level implementation, individual student interventions and teacher focus groups, we offer some recommendations for practice. We present several fun propositions that can help create a culture to support educators as they endeavour to create inclusive educational experiences with emerging technologies. We also explore current trends in technology use, describing and providing practical examples of implementation and integration to support a more inclusive future with emerging technologies.